2018
DOI: 10.1186/s40729-018-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Cast accuracy obtained from different impression techniques at different implant angulations (in vitro study)

Abstract: BackgroundAngulated implants may result in inaccurate impressions, and the impression technique may affect the accuracy of the definitive cast. This study was designed to compare the dimensional accuracy of casts obtained from three impression techniques for three definitive lower casts with implants at different angulations.MethodsThree Osseolink implants were placed in three reference models with different angles (parallel, 15° and 30°). Impressions of each model were made with three techniques (n = 10 per g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 26 publications
3
34
0
2
Order By: Relevance
“…These challenges can be due to the presence of teeth adjacent to implants, an increased number of implants, or alterations to implant orientation [4][5][6]17]. Therefore, in accordance with earlier observations, it can be speculated when the implants are parallel, one specific technique has no advantage over another [10][11][12].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These challenges can be due to the presence of teeth adjacent to implants, an increased number of implants, or alterations to implant orientation [4][5][6]17]. Therefore, in accordance with earlier observations, it can be speculated when the implants are parallel, one specific technique has no advantage over another [10][11][12].…”
Section: Discussionmentioning
confidence: 83%
“…Clinically, the new tray design has multiple potential advantages such as ease of use, simplicity, time efficiency, convenience and less material usage in comparison to the splinting technique. Clinically, however, it is frequently observed that the implants are not parallel and have an angle between them that imposes an extra challenge on the impression, as illustrated in multiple studies [5,[9][10][11][12]. Thus, before a modified tray design can be recommended as a replacement for splinting, it is important to evaluate its accuracy in scenarios that are clinically more relevant, such as the presence of a moderate angle between the implants.…”
Section: Introductionmentioning
confidence: 99%
“…In some of the studies that follow, unlike the present study, the type of splinting material had an impact on the accuracy of the impression. (11)(12)(13)18) Vigolo et al argued that attaching the impression copings using Duralay splinting material is effective in reducing dimensional changes. (13) They used the profile projector method for the assessment of their samples.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers, including Spector et al and Rodney et al have shown that the open tray method is more accurate than the closed tray technique [8]. The type of the impression material, too, affects the accuracy of the final prosthesis; it has been shown that the accuracy of the impression increases with an increase in the hardness of the impression material [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%